Personal Cost and Fraud Seriousness Level to Whistleblowing Intention: the Mediating Role of Organizational Commitment - S R Abdillah; S. P. S. Patiro; R. D. Hadiwidjaja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The revelation of various fraudulent behaviors in the form of corruption cases is based on complaints from the public. There is a very significant difference in public complaint data between the channels at the Komisi Pemberantasan Korupsi (KPK) and the channels at the Balikpapan City Government which can indicate that the level of public trust in the Balikpapan City Government can be said to be still low with regard to their whistleblowing follow-up. This study investigates whether personal cost, the level of seriousness of fraud and organizational commitment play a role in influencing the intention of whistleblowing in the State Civil Apparatus (ASN) related to supervision and internal control at the Regional Apparatus in Balikpapan with organizational commitment as mediation. Before the instrument is deployed, it is first proven that the measurement construct has good discriminant validity and reliability. Furthermore, the hypothesis was tested on 155 respondents representing 164 ASN related to internal supervision and control with a quantitative approach through observation, interviews, and surveys. The main findings of this study include: (1) personal cost does not have a significant effect on organizational commitment; (2) fraud seriousness level affects the organization's commitment; (3) organizational commitment to encourage whistleblowing intentions; (4) personal cost does not have a significant effect on whisteblowing intention; (5) fraud seriousness level does not have a significant effect on the whistleblowing intention; (6) organizational commitment does not mediate the influence of personal cost on whistleblowing intentions; and (7) fraud seriousness level encourages whistleblowing intentions through mediation of organizational commitments. The empirical insights from this study highlight the need for managers to strengthen the organizational commitment of the HR they manage, which is critical to strengthening whistleblowing intent in order to guard organizations from fraudulent behavior. The use of moderation models, testing the power of the mediation effect, generalizations to other regions, inter-cultural comparative studies, the use of technology variables, longitudinal studies, organizational interventions, and in-depth qualitative studies, are recommended for future research on whistleblowing intentions. Keywords : Personal Cost, Fraud Seriousness Level, Whistleblowing Intention, Quantitative Research